Pretreatment with remifentanil protects against the reduced-intestinal contractility related to the ischemia and reperfusion injury in rat - Sayan-Ozacmak,Hale (2015)
BACKGROUND AND OBJECTIVES: Serious functional and structural alterations of gastrointestinal tract are observed in failure of blood supply, leading to gastrointestinal dismotility. Activation of opioid receptors provides cardioprotective effect against ischemia-reperfusion (I/R) injury. The aim of the present study was to determine whether or not remifentanil could reduce I/R injury of small intestine. METHODS: Male Wistar Albino rats were subjected to mesenteric ischemia (30 min) followed by reperfusion (3 h). Four groups were designed: sham control; remifentanil alone; I/R control; and remifentanil + I/R. Animals in remifentanil + I/R group were subjected to infusion of remifentanil (2 ug kg-1 min-1) for 60 min, half of which started before inducing ischemia. Collecting the ileum tissues, evaluation of damage was based on contractile responses to carbachol, levels of lipid peroxidation and neutrophil infiltration, and observation of histopathological features in intestinal tissue. RESULTS: Following reperfusion, a significant decrease in carbachol-induced contractile response, a remarkable increase in both lipid peroxidation and neutrophil infiltration, and a significant injury in mucosa were observed. An average contractile response of remifentanil + I/R group was significantly different from that of the I/R group. Lipid peroxidation and neutrophil infiltration were also significantly suppressed by the treatment. The tissue samples of the I/R group were grade 4 in histopathological evaluation. In remifentanil + I/R group, on the other hand, the mucosal damage was moderate, staging as grade 1. CONCLUSIONS: The pretreatment with remifentanil can attenuate the intestinal I/R injury at a remarkable degree possibly by lowering lipid peroxidation and leukocyte infiltration.